The Effect of Education on the Earnings of Blacks and Whites - Weiss, Randall D. (The Review of Economics and Statistics, 1970)
T HIS paper is concerned with the effect of schooling and learning on the level of workers' earnings. Individual data obtained from the 1/1000 sample of the 1960 United States Census for the North Central region 1 and information on scholastic achievement obtained from Equality of Educational Opportunity,2 popularly known as the Coleman Report, are used to measure the effect of educational achievement and various other personal characteristics on the earnings of those with twelve or fewer years of schooling. The first section discusses the data and the specification of earnings functions. In the next section it is shown that, for whites, a significant relationship exists between an individual's scholastic achievement and his earnings and that achievement explains more of the variance in earnings than does the number of years in school. The third section presents findings that the effect of education on earnings is less for blacks than for whites and that the black's lower average achievement does not account for the difference in the mean earnings of blacks and whites. The fourth section describes a recursive model of income determination.